PENGARUH PUPUK NANOSILIKA TERHADAP PERTUMBUHAN, UKURAN STOMATA DAN KANDUNGAN KLOROFIL CABAI RAWIT (Capsicum frutescens Linn) VARIETAS CAKRA HIJAU - Syella Clarah; Rini Budi Hastuti; Sri Darmanti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
Cayenne pepper is one of horticulture crops that has the benefits and high economic value. Problem often encountered in the cultivation of chili that growth and still low production can not meet consumer demand continues to increase. This causes cayenne prices become relatively expensive in the market. Nutrients silica (Si) role in supporting growth and crop production. Applications use silica has now been developed in the form nanosilica as quickly absorbed by plants and needed in very small amounts. This study aim to assess the effect of nanosilica fertilizer on the growth, size of stomata and content of chlorophyll cayenne pepper. This research was conducted using a Completely Randomized Design (CRD) one factor, that is nanosilica concentration with five treatments: 0 ml/L; 2.5 ml/L; 5 ml/L; 7.5 ml/L; 10 ml/L. The parameters observed are plant height, wet weight, dry weight, number of leaves , size of stomata and content of chlorophyll. The data was analized by Analysis of Variance (ANOVA) and continued with multiple range test Duncan's Multiple Range Test (DMRT) at 95% confidence level. These results indicate that fertilizer nanosilica can increase plant height, wet weight, dry weight, number of leaves and size of stomata Cayenne pepper. N1-N4 treatment tends to improve content of chlorophyll cayenne pepper although not significant by ANOVA. Keyword: Cayenne pepper, growth, nanosilica, stomata, chlorophyll